Implementation of upselling as a strategy in increasing room sales by guest relation host at Alila Seminyak Hotel - Putu Risky Meliarini; Made Sudiarta; Lien Darlina (Politeknik Negeri Bali, 2021)
The purpose of this research is to determine the implementation of upselling as a strategy in increasing room sales at Alila Seminyak hotels and to find out alternative upselling strategies that should be implemented by Guest Relations Hosts in increasing room sales at Alila Seminyak hotels. The analysis technique used is the Sequential Exploratory mixed method design; Internal Factor Summary (IFAS) Matrix, External Factor Analysis Summary (EFAS) Matrix, Internal-External (IE) Matrix, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM). The analysis result of the IFAS matrix with the main strength is that the Alila Seminyak hotel has ten types of rooms that can support upselling activities to guests and can increase room sales, while the main weakness is the lack of providing special prices for guests who upselling. The analysis result of the EFAS matrix is that the main opportunity is the friendliness of the community, environment, and culture around the Alila Seminyak hotel, while the main threat is the tax policy that applies to tourists who are taken into consideration when wanting to upselling. Based on the results of the IE matrix analysis, the Alila Seminyak hotel is in the position of Growth Strategy (Cell II). The results of the SWOT analysis resulted in nine alternative upselling strategies, where three alternative upselling strategies were prioritized which were calculated by the QSPM matrix with a total TAS 232.64, 225.55, and 216.54.